Jionoside A1 alleviates ischemic stroke ischemia/reperfusion injury by promoting Nix-mediated mitophagy: Jionoside A1 promotes Nix-mediated mitophagy - Yu, Xinyuan; Liu, Xiaojun; Mi, Xiujuan; Luo, Xiaoqiong; Lian, Zhiyun; Tang, Jun; Wang, Guixue (Cellular and Molecular Biology, 2023)
In ischemia-reperfusion injury in ischemic stroke, mitophagy, which can remove damaged mitochondria, reduce cytotoxic damage, and enhance neurological recovery, is crucial. Jionoside A1 is a substance found in the traditional Chinese herb Rehmannia glutinosa, which may have neuroprotective effects. The fundamental objective of this work was to find out Jionoside A1's contribution to ischemia/reperfusion injury in ischemic stroke. The oxygen-glucose deprivation/reperfusion (OGD-Rep) model and the right transient middle cerebral artery occlusion (tMCAO) model were established. Jionoside A1 was used for treatment. We utilized a tiny interfering RNA (siRNA) to lower Nix expression. The results suggest that Jionoside A1 may reduce ischemic stroke. By lowering the consequences of ischemia/reperfusion injury, Rehmannia glutinosa can be utilized to treat ischemic stroke. These discoveries provide fresh experimental information for the investigation of ischemic stroke ischemia/reperfusion injury and provide some theoretical justification for their application.